PENGARUH PELAKSANAAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN YANG DIMEDIASI DYSFUNCTIONAL BEHAVIOR DI KABUPATEN SARMI - Westim Ratang (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
This study aims to analyze empirically the effect of the Regional Financial Accounting system on the quality of financial reports, and to analyze empirically the effect of the Regional Financial Accounting system on the quality of financial statements moderated by dysfunctional behavior. The number of samples in this study were as many as 20 people, drawn from all regional apparatus organizations in Sarmi Regency. The results of this study indicate that the regional financial accounting system has a positive effect on the quality of financial reports, the better the implementation of the regional financial accounting system will make the regional financial reports more qualified. The regional financial accounting system has an effect of 37.0% on the quality of financial reports. The regional financial accounting system moderated by dysfunctional behavior has a negative effect on the quality of financial reports. The implementation of the regional financial accounting system if supported by high dysfunctional behavior will reduce the quality of financial reports. The regional financial accounting system which is moderated by dysfunctional behavior has an effect of 60.1% on the quality of financial reports.